Novel Kefir Exopolysaccharides (KEPS) Mitigate Lipopolysaccharide (LPS)-Induced Systemic Inflammation in Luciferase Transgenic Mice through Inhibition of the NF-κB Pathway - Chun-Huei Liao; Chih-Ching Yen; Hsiao-Ling Chen; Yu-Hsien Liu; Yu-Hsuan Chen; Ying-Wei Lan; Ke-Rong Chen; Wei Chen; Chuan-Mu Chen (Antioxidants, 2023)
A novel kefir exopolysaccharides (KEPS) derived from kefir grain fermentation were found to have a small molecular weight (12 kDa) compared to the traditionally high molecular weight (12,000 kDa) of kefiran (KE). KE has been shown to possess antioxidant, blood pressure-lowering, and immune-modulating effects. In this study, we characterized KEPS and KE and evaluated their anti-inflammatory properties in vitro using RAW264.7 macrophages. The main monosaccharide components were identified as glucose (98.1 ± 0.06%) in KEPS and galactose (45.36 ± 0.16%) and glucose (47.13 ± 0.06%) in KE, respectively. Both KEPS and KE significantly reduced IL-6 secretion in lipopolysaccharide (LPS)-stimulated macrophages. We further investigated their effects in LPS-induced systemic injury in male and female NF-κB-luciferase+/+ transgenic mice. Mice received oral KEPS (100 mg/kg) or KE (100 mg/kg) for seven days, followed by LPS or saline injection. KEPS and KE inhibited NF-κB signaling, as indicated by reduced luciferase expression and phosphorylated NF-κB levels. LPS-induced systemic injury increased luciferase signals, especially in the kidney, spleen, pancreas, lung, and gut tissues of female mice compared to male mice. Additionally, it upregulated inflammatory mediators in these organs. However, KEPS and KE effectively suppressed the expression of inflammatory mediators, including p-MAPK and IL-6. These findings demonstrate that KEPS can alleviate LPS-induced systemic damage by inhibiting NF-κB/MAPK signaling, suggesting their potential as a treatment for inflammatory disorders.